Socioeconomic factors and use of secondary preventive therapies for cardiovascular diseases in South Asia: The PURE study. (29th August 2020) - Gupta, Rajeev; Islam, Shofiqul; Mony, Prem; Kutty, V Raman; Mohan, Viswanathan; Kumar, Rajesh; Thakur, JS; Shankar, V Kiruba; Mohan, Deepa; Vijayakumar, K; Rahman, Omar; Yusuf, Rita; et al.
Abstract: Objective: The purpose of this study was to determine the association of socioeconomic factors on use of cardioprotective medicines in known coronary heart disease (CHD) or stroke in South Asia. Methods: We enrolled 33, 423 subjects aged 35–70 years (women 56%, rural 53%, low education 51%, low household wealth 25%) in 150 communities in India, Pakistan and Bangladesh during 2003–2009. Information regarding socioeconomic status, disease conditions and treatments was recorded. We studied influence of rural location, educational status and household wealth on use of drug therapies. Odds ratios (ORs) and 95% confidence intervals were calculated. Results: CHD was reported in 683 (2.0%), stroke 316 (0.9%), and CHD/stroke in 970 (2.9%). Median duration since diagnosis was four years. Participants with CHD/stroke were older with greater prevalence of smoking, overweight, hypertension and diabetes ( p  < 0.01). In patients with CHD, stroke and CHD/stroke, respectively, use (%) of antiplatelets was 11.6, 3.8 and 9.3, beta-blockers 11.9, 7.0 and 10.4, angiotensin-converting enzyme inhibitors or angiotensin receptor blockers 6.4, 1.9 and 5.3 and statins 4.8, 0.6 and 3.5. In CHD/stroke patients any one of these drugs was used in 18.1%, any two in 7.2%, any three in 2.8% and none in 81.5%. Details of drug dose were not available. Use of drugs was significantly lower in rural low education and low wealth index participants (all p  < 0.01). Low wealth index participants had the lowest use of these therapies with no attenuation after multiple adjustments. Conclusion: The use of secondary preventive drug therapies in patients with known CHD or stroke in South Asia is low with over 80% receiving none of the effective drug treatments. Low household wealth is the most important determinant.